Quantitative Descriptive Analysis: The Role Of The Family In The Implementation Of Early Childhood Religious Tolerance - Muhasim Muhasim; Zulfikar Muhammad (DINAMIKA : Jurnal Kajian Pendidikan dan Keislaman, 2026)
The family plays a vital role as the "madrasatul ula" (first school) in shaping the foundation of children's character, including instilling religious tolerance from an early age to prevent discrimination and social conflict in a multicultural society. This study aimed to analyze the role of the family in implementing religious tolerance in early childhood. Employing a quantitative approach with a descriptive design, this study targeted all parents of students at TK Muslimat NU 8 Panggungrejo, Kepanjen, Malang as the population. Sampling was conducted using a purposive sampling technique, resulting in 22 respondents who completed a closed-ended questionnaire (40 statement items) via Google Forms. Data were analyzed using descriptive statistics assisted by IBM SPSS Statistics. The findings revealed that the family's role in implementing religious tolerance in children falls into the High Category. This is evidenced by an overall mean score of 4.23 with a homogeneous standard deviation of 0.56, and an accumulative average total score of 169.27 out of a maximum score of 200 (equivalent to 84.6%). The high involvement of the family is driven by democratic parenting styles, direct parental role modeling aligned with social learning theory, open communication channels, and inclusive family activities. This study concludes that the family serves as a strategic foundation for strengthening character education to foster religious moderation from an early age and maintain social harmony.